ROA, DER, DAN UKURAN PERUSAHAAN PADA AUDIT DELAY - Heni Yusnita (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2024)
The purpose of this study aims to analyze and examine the effect of return on asset, debt to equity ratio, and company size on audit delay in the manufacturing companies of properties and real estate that listed on Indonesian Stock Exchange in 2019-2022, The research method used is quantitative research. The sample selection used purposive sampling method and obtained a sample 35 companies. The result show that return on asset and debt to equity ratio has a negative effect on Audit Delay, while firm size has no effect on audit delay in manufacturing companies of properties and real estate listed on Indonesian stock exchange in 2019-2022. It is hoped that further research can enrich research with other variables such as financial distress, audit tenure and management changes. Future researchers can also use different indicators for the audit delay variable by using dummy variable indicators